Individual Character Transformation Through Human Resource Development: A Multi Disciplinary Approach in Social Studies - Bisr, Hasan; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
This study explores the vital role of human resource development in guiding the transformation of individual character within a dynamic social context. Employing a multidisciplinary approach, the research highlights the intricate interplay between human resource development and individual character development. Through theoretical and practical analyses, the author illustrates how human resource development strategies can significantly contribute to shaping resilient and empowered individual characters in this modern era. The author's findings underscore the importance of integrating social aspects in human resource development efforts to achieve sustainable and meaningful character transformation. This research offers valuable insights for practitioners and researchers interested in understanding the complex relationship between human resource development and individual character formation in contemporary society.